2021
DOI: 10.1007/s40692-021-00183-y
|View full text |Cite
|
Sign up to set email alerts
|

The trends and outcomes of flipped learning research between 2012 and 2018: A descriptive content analysis

Abstract: As an innovative active learning method, flipped learning provides students with several opportunities. This study was conducted to reveal the trends and outcomes in research into the flipped learning approach published between 2012 and 2018. Descriptive content analysis was used to review 316 research and conceptual articles published in academic journals included in five significant databases that ascribe to journals the highest impact factor. The results indicate that most of the studies are conducted with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
57
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(94 citation statements)
references
References 104 publications
4
57
0
4
Order By: Relevance
“…), there are very few studies from the African and Arab regions. Similarly, in BL contexts, Birgili et al 40 conducted a systematic review about flipped learning between 2012 and 2018; they found very few studies coming from Africa. This indicates a trend where countries with more sufficient educational resources and infrastructure are exposed to more chances to develop BL environments and experiences.…”
Section: Resultsmentioning
confidence: 99%
“…), there are very few studies from the African and Arab regions. Similarly, in BL contexts, Birgili et al 40 conducted a systematic review about flipped learning between 2012 and 2018; they found very few studies coming from Africa. This indicates a trend where countries with more sufficient educational resources and infrastructure are exposed to more chances to develop BL environments and experiences.…”
Section: Resultsmentioning
confidence: 99%
“…The upgraded platform continues to use "Internet Classroom". The platform has been also used by businesses for distance learning and for conferencing, the same as Kahoot [44]. The system of iLearn 2.0 module is Moodle.…”
Section: Ilearn 20mentioning
confidence: 99%
“…The challenge in Flipped Classroom is the use and management of technology (Rindaningsih et al, 2019).Students find active learning pedagogy to be an effective method in the classroom. This method also has a positive effect on student achievement, attitudes, cognitive skills, and soft skills because they are more responsible for their own learning (Birgili et al, 2021).…”
Section: Discussionmentioning
confidence: 99%